2021
DOI: 10.1021/acsaem.1c02371
|View full text |Cite
|
Sign up to set email alerts
|

Interface Induced High-Performance Piezoelectric Nanogenerator Based on a Electrospun Three-Phase Composite Nanofiber for Wearable Applications

Abstract: Polymer based composites are the backbone of piezoelectric flexible devices, but the use of toxic compounds or requirement of high voltage poling are the Achilles’ heel of this field. Herein, a lead-free, self-poled, flexible, high performance piezoelectric nanogenerator (PENG) is demonstrated based on a poly­(vinylidene fluoride) (PVDF)–ZnSnO3–MoS2 free-standing electrospun nanofiber mat. ZnSnO3 and MoS2 were synthesized by a hydrothermal route, and a composite nanofiber mat was prepared by the electrospinnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 41 publications
(83 reference statements)
1
46
0
Order By: Relevance
“…Before piezoelectric measurements, samples were poled with a DC field of 10 kV mm −1 under a silicone oil bath at 80°C using an indigenous instrument (Make: Marine India). A digital storage oscilloscope and source meter (Keithley, Tektronix, 2450) was used to obtain voltage outputs from the as‐fabricated harvester by gentle hand tapping with a compressive force of 1 kgf 35 . The measurement process of the force applied by finger tapping is explained in Section S4 of SI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before piezoelectric measurements, samples were poled with a DC field of 10 kV mm −1 under a silicone oil bath at 80°C using an indigenous instrument (Make: Marine India). A digital storage oscilloscope and source meter (Keithley, Tektronix, 2450) was used to obtain voltage outputs from the as‐fabricated harvester by gentle hand tapping with a compressive force of 1 kgf 35 . The measurement process of the force applied by finger tapping is explained in Section S4 of SI.…”
Section: Methodsmentioning
confidence: 99%
“…Further, a reverse polarity test (Figure 6B) was conducted for G-0.16 to confirm the response, free from the electrode and stray effects. 35,59,60 The measured short circuit current (Figure 6E,F From Table 2, it can be observed that the reported works have not studied the complete dielectric, ferroelectric and piezoelectric characterization (with energy harvesting) for such lead-free polymerceramic-graphene three-phase composite. Those with comparable or higher OC voltage and SC current have either larger harvester sizes or are applied with extremely high force, which may not be realistic for powering low-powered devices.…”
Section: Piezoelectric Characterizationmentioning
confidence: 99%
“…[2][3][4] Recently, various piezoelectric materials like ZnO, CdS, ZnSnO 3 , MoS 2 , NaNbO 3 , PbZrTiO 3 (PZT), BaTiO 3 , Zn 2 SiO 4 , Bi 2 WO 6 , KNbO 3 , LiNbO 3 , etc., which have a high piezoelectric charge coefficient, have been synthesized using sol-gel, hydrothermal, physical vapor deposition, and spray polarization techniques, and they have been used to develop piezoelectric nanogenerators. [5][6][7][8] The use of toxic material like lead restricts their use in bio-compatible wearable electronic devices. The piezoelectric performance of the nanogenerator can be improved via several strategies like surface modification, polymerization with polymers, plasma etching.…”
Section: Introductionmentioning
confidence: 99%
“…The piezoelectric nanogenerator (PENG) first proposed by Wang is a novel and smart power source with a simple structure, 7 which can effectively convert the neglected and irregular mechanical energy widely existing in the environment into electrical energy by virtue of the piezoelectric effect of nano-piezoelectric materials. 8−11 In particular, the PENG with its excellent flexibility has attracted widespread attention for its potential applications in some fields, such as wearable electronics devices, 12,13 implantable biomedical devices, 14 and self-powered devices. 15,16 When it comes to nano-piezoelectric materials, they can be classified as the polymer and ceramic piezoelectric materials.…”
Section: Introductionmentioning
confidence: 99%
“…Grafting a high-molecular-weight polymer onto the surface of nanomaterials is a simple and effective measure to enhance the interfacial properties. 13,27 A compatible interface between nanofiller and matrix can be obtained by grafting polymer onto the surface of nanomaterials by atomic transfer radical polymerization (ATRP). Poly(methyl methacrylate) (PMMA) has a higher compatibility with PVDF and better mechanical properties than PVDF.…”
Section: Introductionmentioning
confidence: 99%